2012
DOI: 10.1128/jb.01643-12
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Bacillus oceanisediminis 2691

Abstract: e Bacillus oceanisediminis 2691 is an aerobic, Gram-positive, spore-forming, and moderately halophilic bacterium that was isolated from marine sediment of the Yellow Sea coast of South Korea. Here, we report the draft genome sequence of B. oceanisediminis 2691 that may have an important role in the bioremediation of marine sediment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…The microbe B. oceanisediminis was found to have antimicrobial activity against MDR pathogens. This corroborates the findings of (Lee et al, 2012b) who stated that B. oceanisediminis 2691 is an aerobic, gram-positive, spore-forming, and quite halophilic bac-terium isolated from marine sediments of the Yellow Sea coast, South Korea. It is also known that the design of the genome sequence of B. oceanisediminis 2691 may have an important role in bioremediation of marinesediments.…”
Section: Molecular Phylogenetic Analysissupporting
confidence: 90%
“…The microbe B. oceanisediminis was found to have antimicrobial activity against MDR pathogens. This corroborates the findings of (Lee et al, 2012b) who stated that B. oceanisediminis 2691 is an aerobic, gram-positive, spore-forming, and quite halophilic bac-terium isolated from marine sediments of the Yellow Sea coast, South Korea. It is also known that the design of the genome sequence of B. oceanisediminis 2691 may have an important role in bioremediation of marinesediments.…”
Section: Molecular Phylogenetic Analysissupporting
confidence: 90%
“…Recently, Bacillus oceanisediminis species is a rod-shaped aerobic bacterium, Gram-positive and spore-forming, and first isolated from marine sediment of the South Korean coast. 21 The genus Brevibacillus was reported by Shida 22 with the reclassification of 10 species of the genus Bacillus. A recent study reported that, 25 bacterial isolates were identified by 16S rRNA sequences analysis collected from public tap water in India, from the 25 isolates, 5 were of Bacillus (B. pumilus, B. flexus, B. megaterium, B. marisflavi and B. oceanosediminis).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bacillus oceanisediminis species is a rod-shaped aerobic bacterium, Gram-positive and spore-forming, and first isolated from marine sediment of the South Korean coast. 21 …”
Section: Introductionmentioning
confidence: 99%